Tropheryma whipplei Crystalline Keratopathy: Report of a Case and Updated Review of the Literature - Scott D. Schoenberger; Sumeer Thinda; Stephen J. Kim (Case Reports in Ophthalmological Medicine)
Purpose. To report a case of Tropheryma whipplei infection with crystalline keratopathy and review the recent literature on the presentation, diagnosis, and management of Whipple's disease. Methods. Detailed case presentation and extensive literature search of Pubmed for all years through February 2012 using the following search terms: Whipple's disease, Tropheryma whipplei, corneal deposits, crystalline keratopathy, and uveitis. Relevant articles were retrieved and analyzed. English abstracts were used for non-English articles. Cross-referencing was employed and reference lists from selected articles were used to identify additional pertinent articles. Results. Diagnosis of Whipple's disease remains challenging and untreated infection can result in mortality. Ocular signs and symptoms are usually nonspecific, but several independent cases have reported the presence of intraocular crystals or crystalline-like deposits. Conclusions. The presence of intraocular crystals or crystalline-like deposits may be an identifying feature of ocular Whipple’s disease.